2005
DOI: 10.1158/1055-9965.epi-04-0466
|View full text |Cite
|
Sign up to set email alerts
|

Calcium, Vitamin D, and Apoptosis in the Rectal Epithelium

Abstract: Objective: Decreased apoptosis in the colon is potentially an early indicator of colon cancer risk and may be influenced by calcium and vitamin D. This report describes the associations of calcium intake and 25-hydroxyvitamin D levels with apoptosis in colorectal epithelium. Methods: Consecutive patients undergoing colonoscopies were recruited for a study designed to examine risk and etiologic factors for colorectal adenomas. Diet was assessed by food frequency questionnaire, and in one subpopulation, serum 25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 18 publications
0
28
0
Order By: Relevance
“…Vitamin D status modulates various genes in the colorectal mucosa that may influence the cancer risk (71,80). In humans, vitamin D may induce the differentiation and apoptosis (81,82), both in colorectal adenoma or cancer cells (83) and in the normal colorectal epithelium (84)(85)(86).…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D status modulates various genes in the colorectal mucosa that may influence the cancer risk (71,80). In humans, vitamin D may induce the differentiation and apoptosis (81,82), both in colorectal adenoma or cancer cells (83) and in the normal colorectal epithelium (84)(85)(86).…”
Section: Discussionmentioning
confidence: 99%
“…It is a multifactorial disease that appears to be the result of interacting lifestyle and genetic factors (2)(3)(4)(5)(6)(7)(8)(9). The adenomatous polyp, the precursor to the vast majority of socalled "sporadic" colorectal cancer, currently is the only accepted reliable biomarker of risk for colorectal cancer (8,9), and its removal markedly reduces risk of cancer development.…”
Section: Introductionmentioning
confidence: 99%
“…The lower the level, the higher the risk. The levels of 25-OH-D in Grau et al (2003), Jacobs et al (2006), Miller et al (2005, and Peters et al (2004) demonstrated a significant colorectal cancer or adenoma risk reduction in the range of 27-39.4 ng/ml, with a median of 33 ng/ml. Such a level is well within the normal range of 32-100 ng/ml for 25-OH-D levels.…”
Section: Dose Response Between 25-oh-d Level and Colorectal Cancer Riskmentioning
confidence: 98%
“…Jacobs et al (2006) examined the sample cohort originating from the Ursodeoxycholicacid Trial for adenoma prevention and found a moderate, non-significant inverse association between 25-OH-D levels and adenoma recurrence. Interestingly, Miller et al (2005) revealed that higher 25-OH-D levels were associated with higher rectal epithelium apoptosis for patients with or without adenomas. Peters et al (2004) conducted a nested case-control study within the Prostate, Lung, Colorectal and Ovarian Cancer Screening trial.…”
Section: Dose Response Between 25-oh-d Level and Colorectal Cancer Riskmentioning
confidence: 99%
See 1 more Smart Citation